Eficiência de aplicação do herbicida 2,4-d amina com diferentes volumes e pontas de pulverização - Souza, Lélio Augusto de (2010)
Pesticide spray technology aims the uniform deposition of products in the target, with minimal losses to se soil or drift, which may have consequences in agricultural areas. In this context, the herbicide 2,4-D Amina represents a product with great environmental concern, but still widely used in modern agriculture. Thus, to obtain greater infesting plants control during desiccation, this study evaluated the spray process for the herbicide 2,4-D Amina, with the use of different spray nozzles and volumes, in relation to pesticide deposition, losses to the soil, drift and weed control. The field experiment was done at the research station of Syngenta Seeds Ltd., located in Uberlândia-MG, and the laboratory analyses were done at the Laboratório de Análise de Água do Instituto de Química and at the Laboratório de Mecanização Agrícola do Instituto de Ciências Agrárias, both of Universidade Federal de Uberlândia. The experimental design was randomized blocks with six treatments and four replications, in a total of 24 plots, as a 3x2 factorial: three spray nozzles (drift guard twin flat fan, turbo flat fan and air induction turbo flat fan) and two spray volumes (80 L ha-1 and 130 L ha- 1). Each esperimental unit was 35 m2 (7 x 5 m). The active ingredient used was 2,4-D Amina (at 806 g a.i. L-1) at the dose 1 L c.p. ha-1. A tracer, made of Brilliant Blue food dye (internationally registered by the Food, Drug & Cosmetic as FD&C Blue n.1), at 300 g ha-1, was added to the spray mixture. The spray process was studied by the deposition on the weeds, losses to the soil, and losses by exodrift. Also, the control of weeds on the area was studied. The deposition study, drift and losses to the soil was done by two distinct methods, to determine the relation and agreement between them: direct analysis of the active ingredient 2,4-D Amina, by liquid chromatography (HPLC), and the analysis by quantification of the tracer added to the mixture, using spectrophotometry. According to the results of the experiment, it can be concluded that the spray volume of 80 L ha-1 can be used for weed desiccation with the herbicide 2,4-D Amina, without compromising target coverage; air induction turbo flat fan nozzles promoted greater herbicide loss to the soil; the different nozzles used, with medium, coarse, and very coarse droplets, as well as the spray volumes 80 L ha-1 and 130 L ha-1, did not affect weed control; and the results of the deposition study and losses to the soil, obtained by liquid chromatography were not similar to those obtained by spectrophotometry.